Feminist Modes and Poetics: An Introduction: Exploring the Literary Contributions and Intellectual Capacities of Women (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper entitled “Feminist Modes and Poetics An Introduction” deals with the intellectuality of the fair sex, i.e., the class of the ladies. From time immemorial there was male dominancy in the field of producing literature and sharpening critical standards but times changed progressively and ladies could find ample of pages to express their literal mentality and the prominent class of the male writers had to accept that the ladies are not inferior in any language or may it be any part of the world to show their talent.Critics like Elaine Show walter and others made an analytic study of accounting literal caliber of the ladies in a systematic way. Her work needs appreciation and this research paper also intends to highlight the same that is to establish reputation of the ladies in all possible literal fields may it be drama or poetry or prose.